Corporate Identity, Workspace Atmosphere, and Cultural Expression: Integrating Telkomsel’s Visual Identity into Rattan-Based Interior Design - Tri Prasetyo Utomo; Muhammad Fauzan Ibrahim (Journal of Interdisciplinary Social Sciences and Humanities, 2026)
This study examines the integration of corporate visual identity into interior design through the application of the Telkomsel logo in a rattan-based ceiling pendant lamp within a staff workspace. Moving beyond purely aesthetic considerations, this research explores how interior design functions as a medium for expressing corporate values, shaping spatial experience, and influencing workplace atmosphere. Using a qualitative descriptive approach, data were collected through observation, interviews, and literature review to analyze the design process, material selection, and user responses. The findings reveal that the integration of the Telkomsel logo into a rattan-based lighting design not only enhances visual aesthetics but also strengthens corporate identity and fosters a sense of belonging among employees. Furthermore, the use of rattan as an environmentally friendly material reflects the intersection between sustainability, local material culture, and contemporary corporate design practices. This study highlights that interior design can serve as an interdisciplinary space where branding, cultural expression, and human experience intersect, contributing to both organizational image and workplace well-being.